A lateralidade na música e sua influência no ensino-aprendizado do aluno canhoto de violão. - Maicol Nunes Navarro Freitas (2017)
In musical performance, laterality can be identified in performers who play instruments such as the classical guitar. Im a left-handed and started to study the classical guitar by the right-handed form, this approach indicated by the teacher, without guidance on another way of learning. The present study stems from my personal experience of maladaptation to the right-handedness guitar, resulting in motor limitations experienced by years of instrument study. My problem was solved when I moved from right-to-left to left-to-right approach, which demanded a long and difficult process of readjustment. Thus, this study aimed to influence laterality in the teaching-learning process of the left-handed student of the classical guitar. It integrates a literature review on a laterality and a data collection via questionnaire, answered by four classical guitar teachers who work in the context of higher education of music in Belo Horizonte. The research reached the following conclusions: (1) the left-handed individual is ble to change his laterality, both in practical activities and in the guitar right-handed approach; (2) there is a seemingly remote possibility of any individual not to be able to adapt to the use of the right hand, depending on the activity, which can cause several negative consequences such as laterality treatments in school education. This fact justifies the relevance of studies on laterality for pedagogy of musical instruments and Music Education. So, a more profound understanding of the phenomenon of laterality can act in the prevention of laterality problems in musical instrument students.